Today's story of Jesus - David L. Edwards; Bertello, Guido (London Collins, 1976)
Uses selected passages from the New Testament to relate the events in the life of Jesus.
Keywords: Holy Bible Texts and Translations (3fUhU hJQLeGJ GdcJGH GdebOSs; Christian biography -- Bible -- Palestine